Analyse et contrôle de machine cinématique parallèle hybride - محمد, حمادي; علاء الدين, لعجالي; رضا, زاوي; عبد اللطيف, كنيوة (University of El-Oued, 2022)
This thesis focuses on the optimal design of the hybrid robot with three degrees of freedom, followed by a realization of a geometric and kinetic study of this system. In this study, we selected a robot to obtain the geometric parameters of a machine with hybrid kinematics, we introduce dimensional and kinematic modeling of the chosen structure, and this step remains very important since the performance parameters of a given structure strongly depend on the dimensionality of its geometric parameters. Followed by formulation of the optimization problem taking into account the motor performance as performance criteria. Finally, we present the different stages of building a hybrid robot, with 3D modeling impleتركز هذه الأطروحة على التصميم الأمثل للروبوت الهجين بثلاث درجات من الحرية، متبوعًا بإدراك دراسة هندسية وحركية لهذا النظام. في هذه الدراسة، اخترنا روبوتًا للحصول على المعلمات الهندسية لآلة ذات حركية هجينة، ونقدم نمذجة الأبعاد والحركية للبنية المختارة، وتظل هذه الخطوة مهمة للغاية لأن معلمات الأداء لهيكل معين تعتمد بشدة على الأبعاد من المعلمات الهندسية. تليها صياغة مشكلة التحسين مع الأخذ بعين الاعتبار أداء المحرك كمعايير للأداء. أخيرًا، نقدم المراحل المختلفة لبناء روبوت هجين، مع تنفيذ النمذجة ثلاثية الأبعاد باستخدام برنامج. SolidWorks mented using SolidWorks software.
مذكرة ماستر تخصص كهروميكانيك
Keywords: Parallel Robot, hybrid Robot, Serie Robot, Geometric and Kinematic Model.; روبوت المتوازي، روبوت هجين، روبوت تسلسي، نموذج هندسي وحركي